Predicting Performances on Processing and Memorizing East Asian Faces from Brain Activities in Face-Selective Regions: A Neurocomputational Approach - Shyi, Gary C.-W.; Cheng, Peter K.-H.; Huang, S.-T. Tina; Lee, C.-C.; Tsai, Felix F.-S.; Hsieh, Wan-Ting; Chen, Becky Y.-C. (Frontiers in Human Neuroscience, 2020)
Abstract For more than two decades, a network of face-selective brain regions has been identified as the core system for face processing, including occipital face area (OFA), fusiform face area (FFA), and posterior region of superior temporal sulcus (pSTS). Moreover, recent studies have suggested that ventral route of face processing and memory should end at the anterior temporal lobes (i.e., vATLs), which may play an important role bridging face perception and face memory. It is not entirely clear, however, the extent to which neural activities in these face-selective regions can effectively predict behavioral performance on tasks that are frequently used to investigate face processing and face memory test that requires recognition beyond variation in pose and lighting, especially when non-Caucasian East Asian faces are involved. To address these questions, we first identified during a functional scan the core face network by asking participants to perform a one-back task, while viewing either static images or dynamic videos. Dynamic localizers were effective in identifying regions-of-interest (ROIs) in the core face processing system. We then correlated the brain activities of core ROIs with performances on face processing tasks (component, configural, and composite) and face memory test (Taiwanese Face Memory Test, TFMT) and found evidence for limited predictability. We next adopted a MVPA approach to further explore the predictability of face-selective brain regions on TFMT performance and found evidence suggesting that basic visual processing area such as calcarine and area for structural face processing such as OFA may play an even greater role in memorizing faces. Implications regarding how differences in processing demands between behavioral and neuroimaging tasks and cultural specificity in face processing and memory strategies among participants may have contributed to the findings reported here are discussed.